An audit of stimulant use amongst pre-hospital emergency medical services personnel in Gauteng - Van Rooyen, Ljuba-Ruth (My University, 2021)
Background: Emergency Medical Service (EMS) personnel are exposed to high levels of psychological, physical, and emotional stressors. There has been an increase in stimulant use among healthcare professionals. There is a paucity of data pertaining to the use of stimulant products among EMS personnel in South Africa. We aimed to determine the prevalence and other aspects pertaining to the use of stimulant products among EMS personnel in the Gauteng province of South Africa. Methods: A prospective cross-sectional study using a questionnaire-based model was used to survey EMS personnel in Gauteng. Results: Of the total 315 respondents that completed the questionnaire, 310 (98.4%) reported use of stimulant products, 295 (93.7%) consumed tea/coffee, 187 (59.4%) consumed commercial energy drinks, 60 (19.0%) used caffeinated energy enhancing tablets, 14 (4.4%) used non-caffeinated prescription stimulant medications, 50 (15.9%) used illicit drugs, 134 (42.5%) exceeded the recommended daily allowance of caffeine, 201 (63.8%) exceeded the recommended daily allowance of sugar, 231 (73.3%) experienced difficulty remaining awake during shift, 148 (47.8%) used stimulants off-shift, 71 (22.5%) experienced insomnia. Common reasons for use of stimulants was enjoyment (n=218, 69.2%), to stay awake (n=125, 39.7%) and improvement of physical and mental performance (n=94, 29.8%). Conclusion: The high prevalence of stimulant use amongst respondents is a cause for concern. Strategies to address this should be aimed at promoting awareness and education, improving working conditions, enhancing support structures, and regulating the stimulant content of commercial products.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Emergency Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2021